A case of intraparotid schwannoma in a juvenile: Clinical, pathological, ultrastructural, and immunohistopathological study, including an examination of Ki-67 and MCM-3 expressions. (3rd July 2016) - Zielinski, Rafal; Kobos, Jozef; Zakrzewska, Anna
ABSTRACT: Pleomorphic adenoma, the most common benign nonvascular tumor of the parotid gland in juveniles, should be differentiated from other extremely rare tumors, including schwannoma. In this article, we present a rare case of an intraparotid schwannoma in a juvenile, along with the patient history, a description of pathological features, and the results of ultrastructural and immunohistochemical examination. The respective labeling indexes of Ki-67 and MCM-3, i.e., the mean proportions of positive tumor cells out of 1000 tumoral cells counted in 10 microscopic fields at ×400 magnification, given as a percentage, were found to be 0.82% and 0.4%, respectively.